Luz pulsada e antioxidantes naturais: uma estratégia clean label para reduzir nitrito em produtos cárneos emulsionados - Fracari, Priscila Rossato (2024)
The primary objective of this study was to evaluate the effect of combining pulsed light (PL) and jabuticaba peel extract (JPE) as a clean label strategy to reduce the nitrite content in sliced mortadellas by 50%. The first stage focused on identifying the most effective PL parameters from a microbiological perspective for later application in mortadellas with reduced nitrite content. Different PL parameters were tested, including pulse duration (1260 and 2520 ms), number of pulses (1, 2, and 3), and fluences (6, 9, and 12 J/cm2 ) on sliced mortadellas inoculated with L. monocytogenes. The different PL conditions reduced the L. monocytogenes count by up to 2.3 Log CFU/cm2 . However, a linear relationship between the tested PL parameters and the efficiency of microbial reduction was not observed. The application of PL increased temperature and pH and, in addition, negatively affected the color and oxidative stability of the mortadellas, with more pronounced effects in treatments with a higher number of pulses and fluences. In the second stage, three mortadella formulations were developed: one with 100% nitrite (150 mg/kg) and two with a 50% reduction in nitrite (75 mg/kg), one of which was supplemented with 1% JPE. The sliced mortadellas were treated with PL (12 J/cm2 ), vacuum packaged, and stored at 4 °C for 30 days. The reduction from 150 to 75 mg/kg of nitrite decreased the residual nitrite content by about 50% but increased TBARS values by 200% and the counts of total mesophilic aerobic bacteria (TMAB) and lactic acid bacteria (LAB) by 1.28 and 2.04 Log CFU/g, respectively, after 30 days of storage (P < 0.05). PL reduced (P < 0.05) the counts of TMAB and LAB by up to 1.55 and 2.24 Log CFU/g, respectively, immediately after its application. However, samples with the same nitrite content (without JPE) treated and untreated with PL showed similar TMAB and LAB counts (P > 0.05) at the end of storage. Additionally, PL negatively affected the pH and color, resulting in a sensory perception of "oxidized color" and increased the mortadellas' TBARS values. JPE reduced the defects caused by nitrite reduction and PL application. Furthermore, JPE intensified the antimicrobial effect of PL, resulting in similar TMAB and LAB counts during storage among samples produced with 150 and 75 mg/kg of nitrite.